Find Fergus - Boldt, Mike (New York : Doubleday Books for Young Readers, 2020)
Fergus the bear wants to play hide and seek with the reader, but will need help--and practice--to hide well.
Ages 3-7.
Keywords: Hide-and-seek -- Juvenile fiction; Bears -- Juvenile fiction